STRATEGY FOR IMPLEMENTING THE MERIT SYSTEM IN THE MANAGEMENT OF STATE CIVIL APPARATUS: A CASE STUDY IN THE CITY OF BINJAI - Reza Pirgianta Ginting; Nurliah Nurdin; Bambang Giyanto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Effective government requires professional and quality human resource management. The merit system is the key to increasing government effectiveness and efficiency. This research discusses the implementation of the merit system in the management of state civil servants in Binjai City. Based on policy implementation theory by Charles O. Jones, the three main variables that influence policy implementation are organization, interpretation, and application. This research uses descriptive research using a qualitative approach. data collection techniques using interviews, document review, and field observation. The evaluation carried out shows that although efforts have been made, the implementation of the merit system in Binjai City is considered poor. Strengthening leadership, improving inter-organizational coordination, increasing human resource capacity, effective communication, regular performance evaluation, and response to change are the steps needed to improve the implementation of the merit system. These findings provide important insights for policy makers in formulating more effective strategies in improving the merit system in Binjai City and encouraging the effectiveness of public services.